LOCAL ACTION PLAN - INSTRUMENT FOR SUSTAINABLE RURAL DEVELOPMENT - Bologa, Cătălin Gheorghe (Economics of Agriculture, 2011)
The purpose of this article is to present the concept of sustainable development and highlighting the importance of the Local Action Plan, in rural development. Also are described the principles of local development actors, the factors and the resources of local economic development and their role in the planning and implementation of rural development strategy as well as monitoring and evaluation mechanisms. The last part presents proposals for prioritization, effciency projects and sustainable rural development programs.